Careful Ocular Examination Can Diagnose a Fat Embolism Syndrome - Sujit Das; Sanjeev Verma; Urmi Midya; Devendra Lakhotia (Delhi Journal of Ophthalmology)
Fat embolism syndrome (FES) can develop after a long bone fracture and it has a detrimental effect on life, including death. It usually develops 24–72 h after the incident and classically consists of respiratory distress, petechial rash, and neurological manifestation. Ocular manifestations are rare in FES. Here, we are reporting a case of FES in a patient with lower limb fractures with ocular manifestations of fresh conjunctival bleed, multiple cotton wool spots, and retinal embolism.